Seleksi Lima Jenis Rumput untuk Fitoremediasi Tanah Tercemar Minyak Bumi - Suryati, Tuti (Jurnal Teknologi Lingkungan, 2015)
Phytoremediation is a promising green technology for cleaning up petroleum contaminated soil. The potential of this technology in tropical regions such as Indonesia is very high due to favorable climatic conditions for plant growth and encourage the activity of soil microbes capable of degrading oil. This study aimed to identify five types of grass plants namely Brachiaria decumbens, Brachiaria humidicola, Eleusin indica, Paspalum notatum and Setaria splendida, which were grown in petroleum contaminated soil with Total Petroleum Hydrocarbon (TPH) level of 3.42%. The most important, they are hopefully as the type of grass able to reduce the high petroleum contamination. The results showed that the grass Paspalum notatum was the best candidate for phytoremediation of petroleum contaminated soil, having 43.3%decreased of TPH level after twelve month planting.Keyword : Phytoremediation, petroleum contaminated soil, grasses